Breast feeding, but not use of oral contraceptives, is associated with a reduced risk of rheumatoid arthritis. Issue 4 (13th May 2008) - Pikwer, M; Bergström, U; Nilsson, J-Å; Jacobsson, L; Berglund, G; Turesson, C
Abstract : Objective: To determine whether breast feeding or the use of oral contraceptives (OCs) affects the future risk of rheumatoid arthritis (RA) in a community-based prospective cohort. Methods: A community-based health survey (18 326 women) was linked to regional and national registers, and incident cases of RA were identified. All women with a diagnosis of RA after inclusion in the health survey (n = 136) and four female controls for every case, who were alive and free from RA when the index person was given a diagnosis of RA, were included in a case–control study. Data on lifestyle factors at baseline were derived from a self-administered questionnaire. Potential predictors were examined in logistic regression models. Results: 136 women with incident RA were compared with 544 age-matched controls. A longer history of breast feeding was associated with a reduced risk of RA (OR 0.46 (95% CI 0.24 to 0.91) for women who had breast fed for ⩾13 months and OR 0.74 (95% CI 0.45 to 1.20) for those who had breast fed for 1–12 months, compared with those who had never breast fed). The protective effect of longer breast feeding remained significant after adjustment for smoking and level of education in multivariate models, and point estimates were protective also when the analyses were restricted to parous women. Neither parity nor OC use had any significant effect on the risk of RA. Conclusion: In this study, long-term breast feeding, but not OC use, was associated with a significant reduction in the risk of RA.